How to effectively overcome fixation: a systematic review of fixation and defixation studies on the basis of fixation source and problem type - Wang, Shijun; Okada, Takeshi; Takagi, Kikuko (Frontiers in Education, 2023)
As a cognitive state that impedes idea generation, fixation has been well studied across various domains in relation to the cultivation of creativity. With the aim of contributing to the development of an effective approach to overcoming fixation in order to enhance creativity, a systematic review is conducted of 49 experimental studies concerning the source of fixation and the problem type, which are two critical factors influencing the effectiveness of defixation approaches. Based on the results, it is indicated that an enhancement of the search beyond the frame, constructed by either information that is externally provided or memory that is internally activated by information about the problem, is essential in overcoming fixation. Further, the elimination of fixation leads to an increase in solution rates of closed-ended problems.However, in open-ended problem solving, defixation does not necessarily lead to an improvement in the performance of problem solving, and an advancement can still be achieved by enhancing the search within the constructed frame even when there is no search beyond the frame. Accordingly, an examination of both beyond-frame searches and within-frame searches is essential for an effective defixation approach to enhance creativity in open-ended problem solving.